Anindobothrium n. gen. (Eucestoda: Tetraphyllidea) inhabiting marine and freshwater potamotrygonid stingrays - Marques, F. P.L. [UNESP] (2001)
Anindobothrium n. gen. is proposed to accommodate Caulobothrium anacolum inhabiting Himantura schmardae from Colombia, and 2 new species, one inhabiting Potamotrygon orbigny in Brazil and the other inhabiting Paratrygon aereiba in Venezuela. Members of the new genus resemble members of Pararhineborhroides, Rhinebothroides, and Anthocephalum by having bothridia with poorly differentiated apical suckers and vasa deferentia expanded into external seminal vesicles. It further resembles Pararhinebothroides, Rhinebothroides, and Anthocephalum cairae by having vas deferens inserted near the poral rather than aporal end of the cirrus sac. The 3 species assigned to the new genus form an apparent monophyletic group, based on the possession of 3 putative synapomorphies: (1) genital pores in the anterior 1/4 of the proglottid, a trait that is unusual, but not unique, among phyllobothriids; (2) anteroventral ovarian lobes converging to the center of the proglottid, a character not previously reported for phyllobothriids; and (3) ovarian lobes comprising a loose network of digitiform processes.